DEVELOPMENT OF SOFTWARE FOR QUANTUM VOLTAGE SYNTHESISER - Abubakar, Yusuf (FUDMA JOURNAL OF SCIENCES, 2020)
Signal analysis is a wide area of research, which received considerable attention due to its numerous fields of application. The impact of these fields in technological advancement cannot be overemphasized. No matter how good a signal is acquired, it can still contain some unwanted components (noise) that is capable of undermining its integrity. This work synthesizes signal from a delta-sigma system by designing digital filters LabVIEW program. The designed lowpass and bandpass filters were examined in addition to different filter design algorithms. Based on the analysis, Dolph-chebyshev and Kaiser window filters provide excellent filtering by blocking quantization noise to up to -40dB for fixed point design and, -60dB for floating point. Despite issues with windowing in filter design, these two algorithms seem to work well with this type of signal. Additionally, this design can be optimised by pushing the filter to its limit.